Uji Efektivitas Daun Bawang Dayak (E. Palmifolia) Menggunakan Pelarut Etil Asetat Terhadap Pertumbuhan Staphylococcus Aureus Dengan Metode Sumuran - Jumaqairiah, Siti (Akademi Kesehatan John Paul II Pekanbaru, 2024)
Dayak leek (Eleutherine palmifolia) is one of the plants that is often used by people for traditional medicine in the Kalimantan region. Based on research, Dayak leeks contain alkaloids, flavonoids, saponins and tannins which can function as antibiotics.The aim of this research is to determine the effectiveness of Dayak leeks (Eleutherine palmifolia) using ethyl acetate solvent on the growth of Staphylococcus aureus using the well method. The research design used was true experimental, where this study used a treatment group and a positive control group (clindamycin 2 mcg).The results of the research showed that in the test Dayak leek extract with concentrations of 60%, 65%, 70%, 75% and 80% formed an average diameter of the inhibition zone of 2 mm, 3.8 mm, 4 mm, 4.4 mm and 7 mm in a row. And the control material clindamycin 2 mcg obtained an inhibition zone of 14 mm. So it can be concluded that Dayak leeks can be used as an alternative to antibiotics, especially at high concentrations.Keywords: Dayak leek extract, Staphylococcus aureus, inhibitory power